2004
DOI: 10.1093/ajcn/79.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Plasma kinetics of zeaxanthin and 3′-dehydro-lutein after multiple oral doses of synthetic zeaxanthin

Abstract: Long-term oral intake of 1 and 10 mg zeaxanthin as beadlets increases plasma zeaxanthin concentrations approximately 4- and 20-fold, respectively. Evidence that all-E-3-dehydro-lutein is formed from zeaxanthin was strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 21 publications
2
66
1
Order By: Relevance
“…Thurman et al have also shown this to occur in humans (Thurmann et al, 2005). However, our study is unique in that this conversion was measured without the interference of 3′-dehydro-lutein possibly formed from zeaxanthin (Hartmann et al, 2004). …”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Thurman et al have also shown this to occur in humans (Thurmann et al, 2005). However, our study is unique in that this conversion was measured without the interference of 3′-dehydro-lutein possibly formed from zeaxanthin (Hartmann et al, 2004). …”
Section: Discussionmentioning
confidence: 50%
“…The residue was re-dissolved in100 μL hexane and sonicated for 30 s. A 50 μL aliquot was injected into the HPLC system equipped with an HPLC pump (Waters, 616), an autosampler (Waters, 717 plus, 13°C) and a Photodiode Array Detector (Waters, 996). Carotenoids were quantified using a normal-phase, isocratic HPLC system, as previously described (Hartmann et al, 2004) using a polar column (Lichrosorb, Si-60, 5 μm, 250 × 4 mm; Phenomenex, Torrance, CA, USA) with minor modifications. For optimal separation of lutein and zeaxanthin, the mobile phase ratio hexane (Sigma-Aldrich Chemicals, St. Louis, MO, UAS) to acetone (Sigma, 99.9 % water free) was modified to 85:15 (v/v) at a flow rate of 1 mL/min.…”
Section: Serum Xanthophyll Analysesmentioning
confidence: 99%
See 3 more Smart Citations